TINJAUAN PROSES PERUBAHAN NAMA DI PENGADILAN SEBAGAI HAK INDIVIDU YANG DI CATATKAN NEGARA - Utomo, Abdulah Rafi; Samhudi, Gamalel Rifqi (LPPM STIH Awang Long, 2024)
Name change is an individual right guaranteed by the government, allowing every citizen to manage their personal identity according to their wants and needs. This process must be carried out through formal legal procedures, as stipulated in Law Number 24 of 2013 concerning Population Administration. This study aims to analyze the implementation of name change procedures in Indonesia, focusing on Stipulation number 14/Pdt.P/PN Pbg, which rejected a name change application due to non-compliance with legal procedures. The research method used in the preparation of this study is the normative juridical approach, which specifically focuses on the analysis of norms or the application of principles in applicable law. Based on Law Number 24 of 2013, name changes require a stipulation from the district court according to the applicant's domicile. In addition, Presidential Regulation No. 96/2018 stipulates that the recording of a name change must be accompanied by a copy of the court decision, an extract of the civil registration certificate, a family card, an electronic identity card, and travel documents for foreign nationals. The applicant's application in Stipulation No. 14/Pdt. P/PN Pbg was rejected in relation to the name change application due to non-compliance with applicable legal procedures. The applicant had made several identity changes at the Population and Civil Registration Office without going through the court process, which clearly violated the existing provisions.